Short-term treatment with Alirocumab, flow-dependent dilatation of the brachial artery and use of magnetic resonance diffusion tensor imaging to evaluate vascular structure: an exploratory pilot study - Metzner, Thomas; Leitner, Deborah R.; Dimsity, Gudrun; Gunzer, Felix; Opriessnig, Peter; Mellitzer, Karin; Beck, Andrea; Sourij, Harald; Stojakovic, Tatjana; Deutschmann, Hannes; März, Winfried; Landmesser, Ulf; et al. (Biomedicines, 2022)
Background: Short-term effects of alirocumab on vascular function have hardly been investigated. Moreover, there is a scarce of reliable non-invasive methods to evaluate atherosclerotic changes of the vasculature. The ALIROCKS trial was performed to address these issues using standard ultrasound-based procedures and a completely novel magnetic resonance-based imaging technique. Methods: A total of 24 patients with an indication for treatment with PCSK9 antibodies were recruited. There were 2 visits to the study site, the first before initiation of treatment with alirocumab and the second after 10 weeks of treatment. The key outcome measures included the change of carotid vessel wall fractional anisotropy, a novel magnetic resonance-based measure of vascular integrity, and the changes of carotid intima-media thickness and flow-dependent dilatation of the brachial artery measured with ultrasound. Results: A total of 19 patients completed the trial, 2 patients stopped treatment, 3 patients did not undergo the second visit due to the COVID pandemic. All of them had atherosclerotic vascular disease. Their mean (standard deviation) LDL-cholesterol concentration was 154 (85) mg/dL at baseline and was reduced by 76 (44) mg/dL in response to alirocumab treatment (p < 0.001, n = 19). P-selectin and vascular endothelial growth factors remained unchanged. Flow-dependent dilatation of the brachial artery (+41%, p = 0.241, n = 18), carotid intima-media thickness (p = 0.914, n = 18), and fractional anisotropy of the carotid artery (p = 0.358, n = 13) also did not significantly change. Conclusion: Despite a nominal amelioration for flow-dependent dilatation, significant effects of short-term treatment with alirocumab on vascular function were not detectable. More work would be needed to evaluate, whether fractional anisotropy may be useful in clinical atherosclerosis research.
Gesehen am 11.05.2023